External Shocks and Banking Crises in Developing Countries: Does the Exchange Rate Regime Matter? - Chandima Mendis (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper examines some determinants of banking crises in developing economies. Specifically, the effects of terms of trade shocks and capital flows are analyzed. The choice of the nominal exchange rate regime is found to be a crucial factor in the way various shocks are transmitted through the monetary sector. A logit model is used on panel data and preliminary results indicate that countries with flexible regimes were able to lessen the impact of external shocks on the domestic economy. This in turn reduced the likelihood of banking crises.
Keywords: 330; banking crises; shocks; exchange rates